(3GdSdhc GdHTQj GdeYGUQ aj efXeGJ GdCYeGd (B:s (3GdeaGgje hGdeMOOGJ (B/s - (3eQGRbI, YHO GdZahQs; (3GdUhGdMI, CjhH CMeO s ((3GdLRGFQ(B: s (3OGQ GdCeI ddWHGYIhGdfTQ hGdJhRjY(B, s, 2017)
(3eONd YGe aj GdSdhc GdJfXjej,GdTNUjI GdEfSGfjI heGgjI GdSdhc GdEfSGfj,OhQ GdEOQGc aj HfGA GdSdhc GdJfXjej,CgejI GdGJLGgGJ aj JMOjO GdSdhc GdHTQj,CKQ Gdbje GdJfXjejI Ydi Sdhc GdCaQGO,YdGbI GdOhGaY HGdSdhc GdEfSGfj aj GdefXeI,JCKjQ GdMhGaR Ydi GdSdhc GdHTQj,LeGYI GdYed(B:(3GdCgOGa hGdebheGJ,GdUQGY GdJfXjej(B:(3BKGQg hCSGdjH EOGQJg,GdQVG GdhXjaj(B:(3CgejJg,BKGQg hebGjjSg,CKQ GdhdGA GdJfXjej Ydi GdCOGA GdHTQj,JWhjQ GdPGJ(B:(3eONd CSGSj ddJWhjQ GdJfXjejs
(3HHdjhZQGajG(B:(3U(B.311-327s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdCaQGOs